VESICULATION PROCESSES IN A WATER-RICH CALC-ALKALINE OBSIDIAN - Stevenson R.J.; Bagdassarov N.S.; Romano C. (My University, 1997)
The effect of temperature and viscosity on the kinetics of bubble growth was measured for a natural water-rich rhyolite melt. The change in volume of a natural crystal-poor calc-alkaline rhyolitic obsidian with an initial water content of ~ 1.8 wt% H2O was determined in the temperature interval 520-624°C. Shear viscosity was measured on the natural sample using the micropenetration method in the temperature interval 450-590°C and water contents before and after viscometry were monitored by FTIR. The time-dependence of the volume increase as a result of vesiculation approximates the Avrami equation: ΔV(t) # 1 - exp[ - (t/τ)n]. At temperatures close to the glass transition temperature (Tg), growing bubbles ruptured the surrounding melt. During diffusion of water from the hydrous melt with ~ 1.8 wt% H2O into a bubble, the ΔTg of the melt at the bubble wall increases by ~ 315°C. In addition, the viscosity of the melt at the bubble wall increases by 5-6 orders of magnitude. The increasing elastic component of shear stress on the bubble wall as a result of bubble growth at ~ Tg may exceed the bubble wall yield strength, resulting in cracking. No time lag in the onset of bubble growth occurred for this water-rich rhyolite. In those parts of volcanic edifices where water contents are of several weight percent (e.g., within the upper parts of volcanic conduits), the probability of melt fracturing due to the degassing of water at ~ Tg increases.
Keywords: WATER VAPOR; MAGMAS; VESICULAR TEXTURE; PHASE EQUILIBRIA; VISCOSITY; FRACTURING; MELTS